2013
DOI: 10.1002/adfm.201302359
|View full text |Cite
|
Sign up to set email alerts
|

High‐Performance Dopamine Sensors Based on Whole‐Graphene Solution‐Gated Transistors

Abstract: The authors regret that an older version of Figure 4 was published. The correct Figure 4 is shown here: Figure 4. a) Transfer characteristics (V DS = 0.05 V) of a SGGT with Pt gate electrode measured in PBS solution before and after the addition of dopamine with the concentration of 1 μ M. b) Channel current response of the SGGT to additions of dopamine with different concentrations. V DS = 0.05 V, V G = 0.7 V. Inset: the change of effective gate voltage (Δ V G eff) for different dopamine concentrations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
111
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 151 publications
(114 citation statements)
references
References 54 publications
2
111
0
1
Order By: Relevance
“…Zhang et al reported a SGGT with both channel and gate electrodes fabricated with graphene for dopamine, ascorbic acid and uric acid sensing. [61] Similar to other transistor-based devices, the detection limit was very low for dopamine and sensor selectivity was improved by Nafion modification on the gate. Thus, graphene is an alternative to CNTs for making transistor based sensors.…”
Section: 0 Neurotransmitters/neurochemicalsmentioning
confidence: 83%
“…Zhang et al reported a SGGT with both channel and gate electrodes fabricated with graphene for dopamine, ascorbic acid and uric acid sensing. [61] Similar to other transistor-based devices, the detection limit was very low for dopamine and sensor selectivity was improved by Nafion modification on the gate. Thus, graphene is an alternative to CNTs for making transistor based sensors.…”
Section: 0 Neurotransmitters/neurochemicalsmentioning
confidence: 83%
“…[22][23][24] The increasing interest in dopamine requires facile and reliable sensing techniques, for instance, electrochemical assays and field-effect transistor sensors. [25][26][27][28] The great advantages of electrochemical methods are their detection speed and convenience. However, the selectivity is limited for overlap of oxidation potential of dopamine with many other substances (e.g., ascorbic acid) in central nervous system.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5] However, in the functions of central nervous system, the basal DA concentration is very low (0.01-1 μM). [1][2][3][4][5] However, in the functions of central nervous system, the basal DA concentration is very low (0.01-1 μM).…”
Section: Introductionmentioning
confidence: 99%